Balanced mineral nutrition and application of growth regulators determine productivity and quality of potato - K. V. Vladimirov; A. A. Mostyakova; L. M. Egorov; V. P. Vladimirov (Зерновое хозяйство России, 2018)
There have been studied the response of early maturing potato variety ‘Red Skarlet’ on different methods of application of the growth regulator ‘Albit’ and various rates of mineral nutrition on grey soils of forest-steppe zone of Middle Povolzhie. It has been established that potato treatment by the preparation before planting, double use of the medicine during vegetation and application of both preparations are the most efficient. The experiments were carried out with and without the use of NPK calculated for the potato productivity of 30 t/ha. During the trials we have estimated the dynamics of leaf formation, coefficients of FAR use, productivity and quality of potato. It has been established that the indexes significantly depend on the studied factors. Potato treatment before planting increased the productivity on 1.55-2.10 t/ha depending on the nutrition. Double potato treatment during vegetation increased the productivity on 3.03=3.15 t/ha. The maximum increase of the productivity (4.84-5.10 t/ha) was obtained after a composite use of the preparation.